Strategic Imaginations Women and the Gender of Sovereignty in European Culture - Gilleir, Anke; Defurne, Aude (Leuven University Press, 2020)
What is the gender of political power ? What happens to the history of sovereignty when we reconsider it from a gender perspective ? Political sovereignty has been a major theme in European thought from the very beginning of intellectual reflection on community. Philosophy and political theory, historiography, theology, and literature and the arts have, often in dialogue with one another, sought to represent or recalibrate notions of rule. Yet whatever covenant was imagined, sovereign rule has consistently been figured as a male prerogative While in-depth studies of historical women rulers have proliferated in the past decades, these have not systematically explored how all women rulers throughout the entirety of European culture have had to operate in a context that could not think power as female - except in grotesque terms. Strategic Imaginations demonstrates that this constitutive tension can only be brought out by studying women's political rule in a comparative and longue durée manner. The book offers a collection of essays that brings together studies of female sovereignty from the Polish-Lithuanian to the British Commonwealth, and from the Middle Ages to the genesis of modern democracy. It addresses historical figures and takes stock of the rich yet unsettling imagination of female rule in philosophy, literature and art history. For all the variety of geographical, social, and historical contexts it engages, the book reveals surprising resonances between the strategies women rulers used and the images and practices they adopted in the context of an all-pervasive skepticism toward female rule.